Kajian Tataniaga Beras dan Fluktuasi Harga di Kabupaten Jember - Kuntadi, Ebban Bagus (Jurnal Sosial Ekonomi Pertanian, 2007)
The research was conducted a work of marketing research. It aimed to know distribution of rice among farmer to costumer. The result of the research showed that chain marketing distribution of rice consist of : 1) long and abort chain marketing distribution, 2) marketing margin of rice eficient, 3) share of profit on rice marketing is eficient.Â Kata Kunci : Tataniaga, fluktuasi harga, saluran pemasaran